SEDIMENTOLOGICAL STUDIES OF THE MUKDADIYA FORMATION SOUTH—EAST OF BADRA - Al-Shammary, Thamer (Iraqi Journal of Science, 2024)
The upper of Mukdadiya Formation (Pliocene), which exposed south-east of Badra on the west of the anticline. This part of the Formation ranging between 80m to 120m in the study area. Two sedimentolgical sections were studied in the area. The Formation composed mainly of clastics sediments. These clastics consist of conglomerate, sandstone and mudstone facies.The conglomerate facies mostly are with trough cross bedding and normal graded bedding. The matrix content decrease upwards within the conglomerate beds. The sandstone facies is mostly of very coarse to coarse sand grains, andmostly with trough cross bedding. The bed thickness of the both above facies varies vertically and laterally from one location to another as well as in the same section. The mudstone shows no sedimentary structures and constant thickness, most of the mudstone beds have light brown color; few clay beds have light green color. The conglomerate facies with normal graded bedding represent the channel river deposits while large scale trough cross bedding conglomerate beds represent the longitudinal channel bar deposits, and the trough cross bedding sandstone facies represent a typical river channel point bars deposites.The mudstone beds are river flood plain deposits. The conglomerate, sandstone and mudstone facies repetitions in number of cycles in all the studied section indicate that these deposits are production of braided rivers, the bed thickness and the trough cross bedding size and pebble size as well as the sand content is very good indication of typical variation of braided rivers activities throw the deposition time.